Asnād va mavād somīn Plenūm Shūrā-yi Markazī Jabhah-ʼi Millī Pidar-i Vaṭan, J.D.A., Kabūl 25 Jūzay 1362 (Markazī Jabhah-ʼi Millī Pidar-i Vaṭan, 1984)
Report of the third plenary session of the National Council of Afghanistan, supporting the Karmal regime.